Enhancing 4C Skills Through Project-Based Learning: A Needs Analysis and Impact Study in Cosmetology Education - Laila Fajri; Rahmiati Rahmiati; Linda Rosalina; M. Giatman; Prima Minerva (AL-ISHLAH: Jurnal Pendidikan, 2025)
This study investigates the implementation of Project-Based Learning (PjBL) to enhance 21st-century skills—specifically the 4Cs: Critical Thinking, Creativity, Communication, and Collaboration—in Cosmetology courses at the Department of Cosmetology and Beauty. Preliminary analysis revealed key challenges, including over-reliance on printed materials and limited use of interactive media, which hinder the development of these essential competencies. Using Plomp’s development model, the research involved a needs analysis to assess student learning characteristics and identify gaps. The PjBL approach was then designed and implemented in alignment with these findings. Data were collected through pre-tests and post-tests to evaluate skill development before and after PjBL integration. The findings indicate substantial improvement across all four skill areas following PjBL implementation. Critical thinking improved from 60% to 85%, creativity from 65% to 88%, communication from 58% to 80%, and collaboration from 62% to 84%. The average increase in overall 21st-century skill competency was 69.12%. Although the results demonstrate significant progress, further refinement is needed to sustain and deepen these skills. Strengthening these competencies is essential for preparing students to meet the demands of the increasingly competitive beauty industry. This study underscores the value of integrating PjBL into vocational curricula and highlights its potential to support holistic skill development. The findings contribute to the ongoing discourse on curriculum enhancement in alignment with industry expectations.